Answer:
Step-by-step explanation:
Several trig identities are involved in the proof of this. This is the order in which they are used.
- cos(2x) = cos²(x) -sin²(x)
- cos²(x) +sin²(x) = 1
- cos(x) = 1/sec(x)
<h3>Proof</h3>
Starting with the left side, we can transform it into the right side.
Answer:
Looking at the graphic, if a 45-45-90 triangle has a hypotenuse of 1, then each of the side lengths equal 1 / square root (2)
Source: https://www.1728.org/trig2.htm
Step-by-step explanation:
Answer:
-2
Step-by-step explanation:
You make x= -3 then you insert it into the problem which is x= 2(-3)+4
2 times -3 is -6 which then you would get
-6+4 which equals -2